Sintesis Dan Uji Aktivitas Antioksidan Senyawa Flavonol 2-(3,4,5-Dimetoksifenil)-3-Hidroksi-4h-Kromen-4-On - Muhamad Rokhim; Adel Zamri; Hilwan Yuda Teruna (JURNAL FARMASI DAN MAKANAN, 2019)
Flavonols derivatives of 2'-hydroxycalone have been synthesized under basic condition (KOH). The structures of all compounds were characterized based on the interpretation of spectroscopic data including HPLC, UV, FTIR, NMR and HRMS. Antioxidant activity was evaluated using the DPPH assay which showed that the flavonol 2'-hydroxycalone derivative was potentially active as antioxidants with IC50 values <1000 Âµg / mL.